Decentralised planning in Zimbabwe: a review of provincial urban and district development planning in post-dependence Zimbabwe (Post-1980) - Wekwete, Kadmiel H. (Wiley, 2016)
The paper provides a detailed analysis of the nature and forms of decentralised planning existing in Zimbabwe since 1980. Most of them reflect a continuity from the colonial period with modifications t o suit the new socio- economic order. A detailed review is made of the powers that exist for planning and implementation, and also their limitations. The multiplicity of agencies has created problems, which has called for more co-ordination particularly at provincial level. However, the conflict between territory and function is very evident, because in all cases it is planning either by sector ministries and parastatal agencies with limited territorial power, or in some cases relative autonomy exists for local planning and implementation. The conclusion to this paper is that there is a strong need for a central authority to co-ordinate decentralised planning. This is a contradiction, if one sees decentralisation as the opposite of centralisation. Here we see the co-existence of the two as inevitable because Zimbabwe is a unitary state which defines the limits of decentralisation.